2020
DOI: 10.3390/nu12020389
|View full text |Cite
|
Sign up to set email alerts
|

Postbiotics for Preventing and Treating Common Infectious Diseases in Children: A Systematic Review

Abstract: Postbiotics have recently been tentatively defined as bioactive compounds produced during a fermentation process (including microbial cells, cell constituents and metabolites) that supports health and/or wellbeing. Postbiotics are currently available in some infant formulas and fermented foods. We systematically reviewed evidence on postbiotics for preventing and treating common infectious diseases among children younger than 5 years. The PubMed, Embase, SpringerLink, and ScienceDirect databases were searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 51 publications
(57 reference statements)
1
53
0
2
Order By: Relevance
“…Based on the above, we consider that the administration of heat-killed Lactobacillus casei IMAU60214 by adjuvant therapy, together with oral hydration solutions, could help malnourished patients with conditions complicated by diarrhea, who represent a high risk of mortality with respect to malnourished patients without diarrhea during their stay in Hospital. These conditions are in agreement with the previous reports that suggested that heat-killed bacteria retain immunostimulatory properties [ 63 , 64 ] and their function as potential bioactive foods in the prevention of infectious diseases in children [ 65 ]. However, further research is necessary to extend these observations with well-controlled clinical studies before their acceptance as a recommendation for alternative therapy.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the above, we consider that the administration of heat-killed Lactobacillus casei IMAU60214 by adjuvant therapy, together with oral hydration solutions, could help malnourished patients with conditions complicated by diarrhea, who represent a high risk of mortality with respect to malnourished patients without diarrhea during their stay in Hospital. These conditions are in agreement with the previous reports that suggested that heat-killed bacteria retain immunostimulatory properties [ 63 , 64 ] and their function as potential bioactive foods in the prevention of infectious diseases in children [ 65 ]. However, further research is necessary to extend these observations with well-controlled clinical studies before their acceptance as a recommendation for alternative therapy.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, combining postbiotics and probiotics effectively prevented rotavirus-associated diarrhea in a preclinical model [84]. Furthermore, randomized clinical trials conducted in a group of children aged 12-48 months showed that daily intake of products containing L. paracasei postbiotic led to a reduction in the incidence of diarrhea [85,86], acute gastroenteritis, pharyngitis, laryngitis, and tracheitis [86,87]. Butyrate (a SCFA), was found to support the regeneration of the intestinal epithelium [88].…”
Section: Infection Preventionmentioning
confidence: 99%
“…Similar to probiotics and prebiotics, postbiotics have recently been tentatively defined as bioactive compounds produced during a fermentation process (including inactive microbial cells, cell constituents, and metabolites) that support health and/or well-being [ 52 ]. Postbiotics, particularly heat-killed bacteria, have been widely used in various applications, including foods, cosmetics, and pharmaceuticals.…”
Section: Interventions In the Gut Environment To Enhance Immunity mentioning
confidence: 99%